Johne's disease in cattle: an in vitro model to study early response to infection of Mycobacterium avium subsp. paratuberculosis using RNA-seq. (November 2017) - Marino, Rosanna; Capoferri, Rossana; Panelli, Simona; Minozzi, Giulietta; Strozzi, Francesco; Trevisi, Erminio; Snel, Gustavo G.M.; Ajmone-Marsan, Paolo; Williams, John L.
Highlights: Use of bovine MDM as a cell model for MAP infection. Bovine MDM transcriptome response through a 24 h time course following MAP infection. Cytokine–cytokine receptor interaction, JAK/STAT, antigen presentation, phagocytosis and complement cascade were modulated. Abstract: Johne's disease is a chronic granulomatous enteritis caused by Mycobacterium avium subsp. paratubercolosis (MAP) which affects ruminants worldwide and has a significant economic impact. MAP has also been associated with human Crohn's disease, although this connection is not well established. MAP is highly adapted for survival within host macrophages and prevents macrophage activation, blocks phagosome acidification and maturation, and attenuates presentation of antigens to the immune system. The consequence is a very long silent infection before clinical signs are observed. The present work examined the transcriptome of bovine monocyte-derived macrophages (MDM) infected with the L1 strain of MAP at 2 h, 6 h and 24 h post infection using RNA-seq. Pathway over-representation analysis of genes differentially expressed between infected vs. control MDM identified that immune related pathways were affected. Genes belonging to the c ytokine-cytokine receptor interaction pathway and members of the JAK-STAT pathway, which is involved in the regulation of immune response, were up-regulated. However, in parallel inhibitors of immune functions were activated, including suppressor of cytokine signaling ( SOCS ) and cytokine-inducible SH2-containing protein ( CISH ), which most likely suppresses IFNγ and the JAK/STAT signaling cascade in infected MDM, which may favour MAP survival. After exposure, macrophages phagocytise pathogens, activate the complement cascade and the adaptive immune system through the antigen presentation process. However, data presented here suggest that genes related to phagocytosis and lysosome function are down regulated in MAP infected MDM. Genes of MHC class II and complement pathway were also down-regulated. This study therefore shows that MAP infection is associated with changes in expression of genes related to the host immune response that may affect its ability to survive and multiply inside the host cell.